Study on microbial community of “green-covering” Tuqu and the effect of fortified autochthonous Monascus purpureus on the flavor components of light-aroma-type Baijiu - Zhu, Liping; Li, Lanqi; Yang, Qiang; Chen, Liang; Zhang, Lei; Zhang, Gang; Lin, Bin; Tang, Jie; Zhang, Zongjie; Chen, Shenxi (Frontiers in Microbiology, 2022)
"Green-covering" Tuqu (TQ), as one of Xiaoqu, is a special fermentative starter (also known as Jiuqu in Chinese) that originated in southern China and is characterized by a layer of green mold covering (Aspergillus clavatus) the surface and (sometimes) with a red heart. It plays a vital role in producing light-aroma-type Baijiu (LATB). However, to date, the microbiota that causes red heart of TQ remain largely unexplored, and it is still unclear how these microbiota influence on the quality of LATB. In this study, two types of TQ, one with a red heart (RH) and another with a non-red heart (NRH), were investigated by high throughput sequencing (HTS) and directional screening of culture-dependent methods. The obtained results revealed the differences in the microbial communities of different TQ and led to the isolation of two species of Monascus. Interestingly, the results of high performance liquid chromatography (HPLC) detection showed that citrinin was not detected, indicating that Monascus isolated from TQ was no safety risk, and the contents of gamma-aminobutyric acid in the fermented grains of RH were higher than that of NRH during the fermentation. Selecting the superior autochthonous Monascus (M1) isolated from the TQ to reinoculate into the TQ-making process, established a stable method for producing the experimental "red heart" Tuqu (ERH), which confirmed that the cause of "red heart" was the growth of Monascus strains. After the lab-scale production test, ERH increased ethyl ester production and reduced higher alcohols production. In addition, Monascus had an inhibitory effect on the growth of Saccharomyces and Aspergillus. This study provides the safe, health-beneficial, and superior fermentation strains and strategies for improving the quality of TQ and LATB.